From letters to composed concepts: A magnetoencephalography study of reading. Issue 15 (17th August 2021) - Flick, Graham; Abdullah, Osama; Pylkkänen, Liina
Abstract: Language comprehension requires the recognition of individual words and the combination of their meanings to yield complex concepts or interpretations. This combinatory process often requires the insertion of unstated semantic material between words, based on thematic or feature knowledge. For example, the phrase horse barn is not interpreted as a blend of a horse and a barn, but specifically a barn where horses are kept. Previous neuroscientific evidence suggests that left posterior and anterior temporal cortex underpin thematic and feature‐based concept knowledge, respectively, but much remains unclear about how these areas contribute to combinatory language processing. Using magnetoencephalography, we contrasted source‐localized responses to modifier‐noun phrases involving thematic relations versus feature modifications, while also examining how lower‐level orthographic processing fed composition. Participants completed three procedures examining responses to letter‐strings, adjective‐noun phrases, and noun–noun combinations that varied the semantic relations between words. We found that sections of the left anterior temporal lobe, posterior temporal lobe, and cortex surrounding the angular gyrus were all engaged in the minimal composition of adjective‐noun phrases, a more distributed network than in most prior studies of minimal composition. Of these regions, only the left posterior temporal lobe was additionally sensitive to implicit thematic relations between composing words, suggesting that it houses a specialized relational processing component in a wider composition network. We additionally identified a left occipitotemporal progression from orthographic to lexical processing, feeding ventral anterior areas engaged in the combination of word meanings. Finally, by examining source signal leakage, we characterized the degree to which these responses could be distinguished from one another using source estimation. Abstract : Language comprehension requires the recognition of individual words and the combination of their meanings to yield complex concepts or interpretations. Here, using magnetoencephalography, we provide evidence that a distributed network of left hemisphere areas, including superior sections of the anterior and superior temporal lobe, cortex around the angular gyrus, and anterior sections of the fusiform gyrus, all contribute to the combination of word meanings in reading, in minimal phrases (e.g., red + boat). Within this network, the left posterior temporal lobe appears to be specialized for processing relational knowledge that is relevant to the ongoing combination of words.